2006
DOI: 10.1128/aac.01640-05
|View full text |Cite
|
Sign up to set email alerts
|

Reverse Engineering Antibiotic Sensitivity in a Multidrug-Resistant Pseudomonas aeruginosa Isolate

Abstract: Antibiotic resistance is a pervasive and growing clinical problem. We describe an evaluation of a reverse engineering approach for identifying cellular mechanisms and genes that could be manipulated to increase antibiotic sensitivity in a resistant Pseudomonas aeruginosa isolate. We began by chemically mutating a broadly resistant isolate of P. aeruginosa and screening for mutants with increased sensitivity to the aminoglycoside amikacin, followed by performing whole-genome transcriptional profiling of the mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 93 publications
1
4
0
Order By: Relevance
“…We confirmed the increased resistance of the clones T2-C1, G16-C1, and G16-C2 to aminoglycosides in Luria-Bertani broth. We also confirmed that a previously characterized P. aeruginosa strain, B1 [30] , that has been found to have increased resistance to aminoglycosides in Luria-Bertani broth, maintained the elevated resistance levels in EZ RDM.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…We confirmed the increased resistance of the clones T2-C1, G16-C1, and G16-C2 to aminoglycosides in Luria-Bertani broth. We also confirmed that a previously characterized P. aeruginosa strain, B1 [30] , that has been found to have increased resistance to aminoglycosides in Luria-Bertani broth, maintained the elevated resistance levels in EZ RDM.…”
Section: Resultssupporting
confidence: 86%
“…A definitive link between O-antigens and aminoglycoside resistance has yet to be established, though there have been studies supporting the idea of altered or increased amounts of O-antigen structures could increase resistance levels to aminoglycosides. The expression of O-antigen biosynthesis and assembly genes have been found to have a 2- to 4 log-fold decrease in expression between amikacin-sensitive mutants generated from an aminoglycoside-resistant clinical isolate of P. aeruginosa compared to the resistant parent isolate [30] .…”
Section: Discussionmentioning
confidence: 99%
“…The CARD-RGI analysis supports these results, showing comparable gene presence and abundance. Genes such as mecA, mecR1, blaZ , and femA are consistently detected across all samples by both Solu Bio and CARD-RGI 47,48,49,50,51,52.…”
Section: Resultsmentioning
confidence: 90%
“…HB3267 sensitivity and KT2440 resistance to amikacin may be explained by multifactorial differences in expression of chromosomal genes involved in cell permeability, LPS synthesis, efflux pumps and chemical modification [48] . Vaziri et al (2011) described the existence of aminoglycoside modifying enzymes that are encoded by plasmids as the primary resistance mechanism employed by P. aeruginosa against these antibiotics [49] .…”
Section: Resultsmentioning
confidence: 99%